Funk & Wagnalls new encyclopedia of science. ([New York] : Funk & Wagnalls ; Milwaukee, Wis. : Inquires to Raintree Pub., 1986)
Contains illustrated, alphabetically-arranged articles on a variety of scientific topics. Also includes a volume of related projects and activities.
Keywords: Science -- Encyclopedias, Juvenile; Science -- Encyclopedias